Implementación de un sistema automatizado para el llenado y vaciado de un líquido en un tanque cilíndrico horizontal - Dávila Rengifo, Leonardo Mykel (2024)
The general objective of the present thesis was: implementing a system automated for the filling and draining of a liquid in a cylindrical horizontal tank; determining firstly the relation between the volume with the level of liquid, which made suitable itself and programmed in Microsoft Excel 2023 to determine the initial volume and the experimental value of the final volume of liquid. The implementation of the automated system was the following: a programmable relay, two push-buttons NC, two push-buttons NO, two lights led, a thermic key with its bipolar plug, a viewfinder with gauged rule, a line filling (shaped for spans of piping and accessories, the electric pumps filling and a meter of volume) and a line draining (shaped for spans of piping and accessories, the electric pumps draining and a meter of volume). Straightaway, became elaborate the diagram ladder for the automatic control of the filling and draining of a liquid in a cylindrical horizontal tank, which allowed determining the number of inputs and physical outputs that were used of the programmable relay, the same that gave results: four inputs and two physical outputs. At last, five (5) proofs for the filling and five (5) for the draining came true. The minimum (0.205 %) and maximum (1.384 %) percentage error regarding the final volume of liquid, they obtained in the proofs 4 and 5 of the operation of draining, respectively. The present thesis has this way been culminated, coming true with the objective general and the time trying on his general hypothesis.